A Hierarchical Privacy Preserving Pseudonymous Authentication Protocol for VANET - Ubaidullah Rajput; Fizza Abbas; Heekuck Oh (IEEE Access, 2016)
Vehicular ad hoc network (VANET) is a technology that enables smart vehicles to communicate with each other and form a mobile network. VANET facilitates users with improved traffic efficiency and safety. Authenticated communication becomes one of the prime requirements of VANET. However, authentication may reveal a user's personal information such as identity or location, and therefore, the privacy of an honest user must be protected. This paper proposes an efficient and practical pseudonymous authentication protocol with conditional privacy preservation. Our protocol proposes a hierarchy of pseudonyms based on the time period of their usage. We propose the idea of primary pseudonyms with relatively longer time periods that are used to communicate with semi-trusted authorities and secondary pseudonyms with a smaller life time that are used to communicate with other vehicles. Most of the current pseudonym-based approaches are based on certificate revocation list (CRL) that causes significant communication and storage overhead or group-based approaches that are computationally expensive and suffer from group-management issues. These schemes also suffer from trust issues related to certification authority. Our protocol only expects an honest-but-curious behavior from otherwise fully trusted authorities. Our proposed protocol protects a user's privacy until the user honestly follows the protocol. In case of a malicious activity, the true identity of the user is revealed to the appropriate authorities. Our protocol does not require maintaining a CRL and the inherent mechanism assures the receiver that the message and corresponding pseudonym are safe and authentic. We thoroughly examined our protocol to show its resilience against various attacks and provide computational as well as communicational overhead analysis to show its efficiency and robustness. Furthermore, we simulated our protocol in order to analyze the network performance and the results show the feasibility of our proposed protocol in terms of end-to-end delay and packet delivery ratio.